The Sources of Wage Growth in a Developing Country - Ioana E. Marinescu; Margaret Triyana (Institute for the Study of Labor (IZA), 2015)
What are the sources of wage growth in developing countries? In the US, general labor market experience is the key source of wage growth, with job seniority playing a smaller role. By contrast, in Indonesia, the 10-year return to seniority is 24 to 29%, which is higher than the return to experience. Furthermore, we estimate a 35% return to ten years of tenure in the formal sector, with no significant return to tenure in the informal sector. The difference in the sources of wage growth in Indonesia versus the US may be a reflection of Indonesia's lower level of development.
Keywords: J31; O1; 330; experience; formality; informality; wages; tenure